Development and Evaluation of the Breast Cancer Online Rehabilitation (BRECOR) Program for Self-managed Upper-Body Rehabilitation for Women With Breast Cancer. Issue 3 (July 2019) - Rafn, Bolette S.; Nees, Carina; Midtgaard, Julie; Camp, Pat G.; Vibe-Petersen, Jette; Campbell, Kristin L.
Abstract : Background: Survivors of breast cancer experience upper-body issues. Objectives: To develop and evaluate a rehabilitation program (BRECOR) to support self-managed upper-body rehabilitation after treatment for breast cancer. Design: Development and feasibility study. Setting: Community-based. Participants: Development of program elements (clinical assessment tool, education pamphlet, and Website) was informed by 17 physical therapists with experience in oncology rehabilitation and 10 women with breast cancer. Feasibility was evaluated by 35 women who had recently undergone surgery for breast cancer and 29 women who had completed surgery and radiation therapy for breast cancer. Intervention: Participants performed an individualized 12-week self-managed upper-body rehabilitation program informed by the clinical assessment tool, with support from the education pamphlet and the Website. Measurements: Recruitment/retention rates, adherence, capacity, and participant satisfaction were collected to establish feasibility. Results: Feedback from the physical therapists was instrumental in developing the program content. User testing refined the program elements. Participant feedback in the feasibility testing was positive with good recruitment (80%), retention (83%), and adherence (72%) to the self-managed upper-body rehabilitation program. Participants improved their upper-body function and reported benefit from the program. Limitations: The effectiveness of the BRECOR program in improving upper-body function cannot be determined, as this was a single-group feasibility study. Conclusion: A feasible, self-managed upper-body rehabilitation program was developed through iterative stages of program development and feasibility testing. The BRECOR program elements provide a toolkit to enforce qualified upper-body assessment, provide rehabilitation prescriptions, and support self-managed upper-body rehabilitation after treatment for breast cancer.